T-regulatory cells require Sin3a for stable expression of Foxp3 - Christensen, Lanette M.; Akimova, Tatiana; Wang, Liqing; Han, Rongxiang; Samanta, Arabinda; Di Giorgio, Eros; Hancock, Wayne W. (Frontiers in Immunology, 2024)
Histone deacetylases 1 and 2 play a major role in the transcriptional regulation of T-regulatory (Treg) cells via interactions with a myriad of coregulatory factors. Sin3a has been well established as a Hdac1/2 cofactor, while its role within Tregs has not been established. In this study, the effects of conditional deletion of Sin3a within Foxp3+ Tregs were evaluated. Developmental deletion of Sin3a from Foxp3+ Tregs resulted in the rapid onset of fatal autoimmunity. Treg numbers were greatly reduced, while residual Tregs had impaired suppressive function. Mice also showed effector T-cell activation, autoantibody production, and widespread tissue injury. Mechanistically, Sin3a deletion resulted in decreased transcription of Foxp3 with a complete lack of CNS2 CpG demethylation. In addition, Foxp3 protein stability was impaired with an increased ex-Treg population. Thus, Sin3a plays a critical role in the maintenance of Treg identity and function and is essential for the expression and stability of Foxp3.